Penumbuhan Jiwa Wirausaha Siswa SMK Ma’arif NU 01 Wanasari Melalui Pelatihan Pengolahan Limbah Air Kelapa - Muhamad Hasdar; Abdul Bashar; Wadli Wadli (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2019)
Entrepreneurship development among productive young people is a strategic program to build young entrepreneurs who have quality human resources. Vocational students are a strategic choice for building young entrepreneurs. The purpose of this community development activity is 1) Building strong character, because strong character becomes the main capital to become an entrepreneur in facing the challenges of changes that occur in his life. 2) Vocational students have skills to process coconut water waste into nata de coco. 3) Vocational students can start opening new business opportunities either before or after graduating later. The partners of this activity are students from SMK Ma'arif NU 01 Wanasari who are selected 20 students, their have an interest in food entrepreneurship. This activity was carried out in four stages for 2 months. Activities are divided into 4 stages. stage I is measuring the level of understanding from the students about entrepreneurship by giving quisioners, stage II is a process transfer knowlegde with the lecture method, stage III is carried out with the practice of directly using appropriate technology, stage VI is the evaluation stage of activities with quisioner and lecture methods. All vocational students participate in all stages of the training well, with this entrepreneurship training vocational students have increased skills and knowledge in entrepreneurship. Through these activities vocational students also have the skills to process coconut water waste into nata de coco until the packaging process is ready to be marketed and vocational students have basic knowledge about starting entrepreneurship in the food sector. Based on the evaluation results of entrepreneurship training activities, Vocational students are very happy and satisfied and in accordance with the expectations of SMK students to build their entrepreneurial spirit.